Does codon composition influence ribosome function? - Andersson, S G (1984)
Escherichia coli ribosomes pre-initiated with N-acetyl-Val-tRNAVal elongate strictly alternating poly(U-G) at a rate between eight and 12 peptide bonds per second per ribosome in vitro. Comparisons with poly(U)-primed poly(Phe) synthesis show that these systems function with the same rates which are close to those of protein synthesis in vivo. This indicates that, at least in vitro, codon composition has no marked influence on the speed of elongation when the concentration of ternary complex is saturating. Furthermore, the missense frequencies for the two polymers are within the same range: the missense substitution of Trp for Cys is 10(-4) and that of Met for Val is 10(-3) in the poly(U-G)-primed system. These data argue against models that explain the codon preference of certain gene families by postulating effects of high or low GC content of codons on the performance characteristics of ribosomes.